The minor arts of daily life : popular culture in Taiwan - Jordan, David K.; Morris, Andrew D.; Moskowitz, Marc L. (University of Hawaii Press, 2004)
The Minor Arts of Daily Life is an account of the many ways in which contemporary Taiwanese approach their ordinary existence and activities. It presents a wide range of aspects of day-to-day living to convey something of the world as experienced by the Taiwanese themselves. Contributors: Alice Chu, Chien-Juh Gu, David K. Jordan, Paul R. Katz, Chin-Ju Lin, Andrew D. Morris, Marc L. Moskowitz, Scott Simon, Shuenn-Der Yu.